Mineralogical and geochemical characteristics of barium slag and ecological risks associated with heavy metals - Chengbing Fu; Yu Zhang; Juan Tian; Wenxing Chen; Hongyan Pan; Jianxin Cao (Arabian Journal of Chemistry)
Barium slag (BS) is a typical chemical hazardous waste, and its ecological risks cannot be ignored. Herein, the chemical composition, mineral composition and morphological characteristics of BS were investigated. In addition, the geochemical behaviour was investigated in terms of heavy-metal-leaching toxicity as well as the bioavailability, bioaccessibility and migration of these metals. The ecological risks associated with the release of heavy metals from BS driven by its geochemical behaviour were also evaluated. The BS displayed irregular particle morphologies and distinct surface structures, with heavy metal ions predominantly present in the smaller-sized BS particles. Zn, Ni, Mn and Ba exhibited a stronger potential for migration in plants than other heavy metals. This migration potential was influenced by their total amount and occurrence form as well as the pH conditions of the surrounding environment. The findings indicated that crops should not be planted around BS yards. The bioaccessible risks associated with heavy metals in BS were low. Mn, Ba, Fe and Ni primarily existed in the form of a weak-acid soluble fraction, thereby posing a high migration risk. Thus, attention should be paid to the ecological risks that may arise from Mn, Ba, Fe and Ni during storage.